Peranan Sistem Pelayanan Keselamatan Pelayaran KSOP Terhadap Keselamatan dan Kemanan Kapal Berlabuh di Pelabuhan Tanjung Emas Semarang - Nugraha, Markus Asta Patma; Krishendratna, Marshella (Politeknik Pelayaran Sumatera Barat, 2025)
As governed in Ministerial Regulation No. 33 of 2021, the harbourmaster is a state official at the port with the most authority in managing the safety and security of shipping. This research aimed to analyse the role of Port Authority and Harbourmaster Office (KSOP) Class I Tanjung Emas in ensuring the safety and security of ships anchored at Tanjung Emas Port, Semarang. This research utilizes qualitative methods using observation, interview, documentation, and literature study. The messages report that the functioning of the inaportnet system rationalizes ship arrivals and departures administration, while enforcement of national and international regulations, like the ISPS Code, escalates surveillance and port security. KSOP's function is significant, both as an emergency regulator and coordinator, law enforcement agent, and enforcer of secure and orderly port facilities.